Planning for Happenstance: Helping Students Optimize Unexpected Career Developments - Michelle Vo; Gary Beck Dallaghan; Nicole Borges; Anne C. Gill; Brian Good; Nathan Gollehon; Jay J. Mehta; Boyd Richards; Rachel Richards; Erna Serelzic; Rebecca Tenney-Soeiro; Jason Winward; et al. (Association of American Medical Colleges, 2021)
Introduction Planning for and responding to happenstance is an important but rarely discussed part of the professional development of medical students. We noted this gap while conducting a study of career inflection points of 24 physicians who frequently mentioned how luck had shaped their unfolding careers. A review of the career counseling literature led us to a body of work known as Planned Happenstance Learning Theory (PHLT). PHLT focuses on the attitudes and skills to make happenstance a positive force in one's life. We found no reference to this work in the medical education literature and resolved to address this gap. Methods We created resources for an interactive, 90-minute faculty development workshop. In the workshop, the facilitator used a PowerPoint presentation, vignettes of happenstance, a student testimonial, and a reflection worksheet. We presented and formally evaluated the workshop at three national meetings for health science educators. Results Workshop participants, mostly faculty (N = 45), consistently expressed positive regard for the workshop content, organization, and instructional methods, especially the opportunity for guided reflection. A retrospective pre/postevaluation revealed a meaningful increase in knowledge about PHLT attitudes and skills, as well as a commitment to use these skills in promoting professional development. Discussion The skills and attitudes of PHLT are relevant to students' career development. A workshop designed to introduce PHLT skills and attitudes to faculty advisors and mentors can help prepare faculty to promote students' awareness and use of these attitudes and skills.